PENGARUH PEMBERIAN TIMBAL (Pb) ASETAT PERORAL TERHADAP KADAR GLUKOSA DARAH PADA MENCIT (Mus Musculus)JANTAN Balb/C - Neti Eka Jayanti (ITKES Wiyata Husada Samarinda, 2018)
Several kind of heavy metals that present in the environment are considered as toxic substance to human and animal. Lead (Pb) is one of heavy metals that increase in use for the last decade. Lead toxicity to human had wide in fluence in medical aspect, from nerve problem, bone metabolics disturbance until liver an d renal failure. This experiment tried to found out the effect of cronic oral lead consumtion to lead plasma rate in mice. Design of this experiment is true research experiment to test wheater there is an effect of oral lead consumption to acumulation of lead in blood glucose of mice. The results show increase of lead accumulation in blood glucose of the mice compared to control group.